Bupleuri radix for Acute Uncomplicated Respiratory Tract Infection: A Systematic Review of Randomized Controlled Trials - Yan, Li-Jiao; Wang, Zhi-Jie; Fang, Min; Lan, Hui-Di; Moore, Michael; Willcox, Merlin; Trill, Jeanne; Hu, Xiao-Yang; Liu, Jian-Ping (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy, clinical effectiveness, and safety of the Chinese herb Bupleuri radix for the treatment of acute uncomplicated respiratory tract infections (ARTI). Methods: Four English and four Chinese databases were searched from their inception to June 2021. Randomized controlled trials (RCTs) assessing therapeutic effects of Bupleuri radix on ARTI were eligible for inclusion. The risk of bias for each trial was assessed using the Cochrane Risk of Bias Tool 2.0. RevMan 5.4 software was used for data analyses with effects estimated as risk ratios (RR) or mean differences (MD) with 95% confidence intervals (CI). The certainty of the evidence was assessed using the online GRADEpro tool. Results: Seven randomized trials involving 910 patients with acute upper respiratory tract infection (AURTI) were included. The review identified Bupleuri radix agents with four administration routes (oral, acupoint injection, intramuscular injection, nebulized inhalation). Bupleuri radix acupoint injection compared with placebo showed statistically significant effects in reducing fever resolution time (MD: -33.32 hours, 95%CI: -35.71, -30.93), and in increasing the proportion of participants with fever resolved within 48h from treatment onset (RR: 14, 95%CI: 1.96, 99.94). Bupleuri radix acupoint injection combined with usual care is more effective in reducing the temperature at day 1 from treatment onset (MD:-1.00℃, 95%CI: -1.19, -0.81) compared with usual care alone. However, the oral preparation (pill) failed to demonstrate an effect in reducing fever, as did the injection when compared with antivirals. It suggested that oral administration of Bupleuri radix solution for injections, pill, and Bupleuri radix decoction have a similar effect on improving global AURTI symptoms including two key symptoms (nasal discharge and cough), when compared with usual care alone. Only two trials reported whether or not there were any AEs and found no occurrence of adverse events in the herbal group. Conclusion: Low-certainty or very low-certainty evidence demonstrated that Bupleuri radix injection has an antipyretic effect on febrile patients with AURTI, but it has no effect on other AURTI symptoms. However, these findings need to be further confirmed by well-designed clinical trials with adequate sample sizes. Systematic review registration: PROSPERO registration number: CRD42021234066.